INVEST LIKE AN INSTITUTION PROFESSIONAL STRATEGIES FOR FUNDING A SUCCESSFUL RETIREMENT - Schlachter, Michael C. (Apress : Imprint: Apress, 2013)
All too often, when investors go in search of investment advice, they are met with television personalities and so-called investment gurus who do little more than push the latest and greatest scheme to retire rich. Your retirement fundsin the form of IRAs, 401(k)s, SEP or Simple IRAs, and other plans you can direct to some degreeare, however, far too precious to bet on the latest scheme, trend, or tip you heard at a party. InInvest Like an Institution: Professional Strategies for Funding a Successful Retirement, Michael Schlachter provides individual investors with the tools they need to build a portfolio that not only protects their wealth but helps it grow for the long term. Result? A comfortable retirement in which you can pursue your dreams and check bucket list items off at your leisure. As an advisor to large pension funds and endowments, Michael Schlachter counts among his clients the elite. Institutional investors like the retirement systems of states and major companies, as well as the largest university endowments, are among the few that consistently outperform the market. Sure, average retail investors can't make the same types of private deals in real estate, private equity, or hedge funds that institutional investors use to reap large returns or offset market volatility. But as this book demonstrates, youcanreplicate in your own portfolio the very same diversification strategies that large funds employ to achieve long-term gains. To that end, Invest Like an Institution shows how to build a portfolio that is every bit as diversified and risk-controlled as a multi-billion-dollar institutional fundand a portfolio more likely to result in a happy, financially secure retirement. Filled with easy-to-implement guidelines that will put you on the path to financial success without encouraging you to chase trends, take on unneeded risks, or spend unnecessary fees,Invest Like an Institutionanalyzes: Why asset allocation and consistent retirement contributions are the single largest determinant of your success or failure The merits of a global portfolio versus those of a home countrybiased portfolio How newer investment strategies are used by institutional investors to supplement a well-diversified portfolio Why fixed income investments are not as safe as most investors think and how to understand their role in your portfolio The best alternative asset classes that are readily available to individual investors Invest Like an Institution will help ensure that your investments are positioned for long-term growth under any market conditions. Follow its advice, and you can better achieve a prime goal we all share: retiring with a substantial nest egg.